Perfis de tensão residual do aço duplex UNS S32304 submetido a diferentes processos de soldagem TIG e condições de tratamento térmico - Machado, Caruline de Souza Carvalho (2015)
Aiming the implementation of duplex UNS S32304 steel as a packed for radioactive material transport, TIG welded samples, with different shielding gas, were subjected to heat treatments at different temperatures, 475 °C, 600 °C and 750 °C, for 8 hours followed by air cooling, in order to examine the critical temperatures effect on the steel residual stress profile and microestruture. The X-ray diffraction was used as a non-destructive technique to determine the residual stresses at different conditions (samples received and only heat treated) and the profile of the total residuals stresses welded samples is analysed for each phase (austenite and ferrite). The residual stresses of the phases was determined by sen2ψ. For austenite phase it was used CuKα radiation source (<̅ > = 0.1542 nm) and for the ferrite phase it was used CrKα radiation (<̅> = 0.2291 nm). It was also measured the ferrite contents, Vickers microhardness and microstructure of the materials was investigated. These results were related to the obtained profiles. It was found that both, the temperature and the variation of the shielding gas, influence on the stresses profile for the different phases in the steel.